2024
DOI: 10.3389/fendo.2023.1315520
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 affects calcium signalling predominantly during activation and activity of beta cell networks in acute mouse pancreas tissue slices

Eva Paradiž Leitgeb,
Jasmina Kerčmar,
Lidija Križančić Bombek
et al.

Abstract: Tight control of beta cell stimulus-secretion coupling is crucial for maintaining homeostasis of energy-rich nutrients. While glucose serves as a primary regulator of this process, incretins augment beta cell function, partly by enhancing cytosolic [Ca2+] dynamics. However, the details of how precisely they affect beta cell recruitment during activation, their active time, and functional connectivity during plateau activity, and how they influence beta cell deactivation remain to be described. Performing funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 143 publications
1
3
0
Order By: Relevance
“…The precise protocol and the average unprocessed Ca 2+ signal of all cells is shown in Fig 3A . Previous research has demonstrated that Ex-4 increases the density of functional beta cell networks [ 71 ], and our results validate this observation under both fixed threshold R th and fixed average degree k avg methods ( Fig 3B ). However, the fixed R th approach encapsulates substantial heterogeneity among islets, obscuring the effects of Ex-4 stimulation when aggregating data across multiple islets, despite discernible trends at the individual islet level.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The precise protocol and the average unprocessed Ca 2+ signal of all cells is shown in Fig 3A . Previous research has demonstrated that Ex-4 increases the density of functional beta cell networks [ 71 ], and our results validate this observation under both fixed threshold R th and fixed average degree k avg methods ( Fig 3B ). However, the fixed R th approach encapsulates substantial heterogeneity among islets, obscuring the effects of Ex-4 stimulation when aggregating data across multiple islets, despite discernible trends at the individual islet level.…”
Section: Resultssupporting
confidence: 89%
“…In such scenarios, normalizing the average degree proves to be the superior approach, as it facilitates a robust evaluation of data from different islets. Data used for this analysis is from Ref [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations